2019
DOI: 10.1016/j.bbapap.2019.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Transmembrane topology of mammalian ORMDL proteins in the endoplasmic reticulum as revealed by the substituted cysteine accessibility method (SCAM™)

Abstract: Sphingolipids are diverse lipids with essential, and occasionally opposing, functions in the cell and therefore tight control over biosynthesis is vital. Mechanisms governing this regulation are not understood. Initial steps in sphingolipid biosynthesis take place on the cytosolic face of the endoplasmic reticulum (ER). Serine palmitoyltransferase (SPT) is an ER-resident enzyme catalyzing the first-committed step in sphingolipid biosynthesis. Not surprisingly, SPT activity is tightly regulated. ORMDLs are ER-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…The extent of identity between ORMDL2 and ORMDL3 at the protein level is 83% in mice and 80% in humans ( 7 ). The graphical comparison of the primary amino acid sequence of mouse ORMDL2 and ORMDL3, based on the recently determined topology of ORMDL1 by Davis et al ( 46 ), is shown in Figure 2A . The difference between proteins is subtle, and most of the dissimilar amino acids are in the membrane region.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The extent of identity between ORMDL2 and ORMDL3 at the protein level is 83% in mice and 80% in humans ( 7 ). The graphical comparison of the primary amino acid sequence of mouse ORMDL2 and ORMDL3, based on the recently determined topology of ORMDL1 by Davis et al ( 46 ), is shown in Figure 2A . The difference between proteins is subtle, and most of the dissimilar amino acids are in the membrane region.…”
Section: Resultsmentioning
confidence: 99%
“… The role of ORMDL2 and ORMDL3 and their redundancy in the metabolism of sphingolipids in BMMCs. (A) Left: predicted topology of murine ORMDL2 based on recently described ORMDL1 topology ( 46 ). Residues marked in the murine ORMDL2 by green color indicate conserved amino acids, in red are shown residues which are different in mORMDL3.…”
Section: Resultsmentioning
confidence: 99%
“…Once a protein is conjugated with PEG-maleimide, it becomes larger and can be separated from an unconjugated form by SDS-PAGE (Fig. 5B) (Davis et al, 2019). As PEG-maleimide is cell-impermeable, specific labeling is achieved only after membrane permeabilization with a detergent (Fig.…”
Section: Biochemical Verification Of the Topology Of Tmem41bmentioning
confidence: 99%
“…Interestingly, S1P‐mediated PHD inhibition was, at least in part, mediated by AKT signaling, in agreement with previous studies. Considering the proposed structure of ORMDLs (Davis et al , 2019a), P137 has been predicted to be the penultimate amino acid in the second transmembrane domain, which does not necessarily preclude the accessibility of this amino acids by PHDs. For instance, enzymatic‐mediated palmitoylation of cysteines located inside or close to the transmembrane domain has been shown for several proteins (Charollais & Van Der Goot, 2009).…”
Section: Discussionmentioning
confidence: 99%